Model Penguatan Kapasitas SDM dalam Mendorong Transformasi Kelembagaan Polri melalui Kepemimpinan Visioner, Kompetensi Personel, Budaya Profesional, dan Sistem Pengawasan - Mayastinasari, Vita; Suseno, Bayu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Institutional transformation within the Indonesian National Police (Polri) requires a comprehensive strengthening of human resource capacity as its fundamental foundation. Rapid social changes, rising expectations for public accountability, and increasingly complex forms of modern crime demand the adoption of visionary leadership, enhanced personnel competencies, a strong professional culture, and a transparent, adaptive oversight system. This study analyzes the simultaneous contribution of these four pillars in driving institutional reform within Polri. The research uses a literature review method, drawing from empirical and theoretical studies published over the past decade encompassing police leadership, human resource management, organizational culture, and oversight mechanisms. The findings show that visionary leadership provides a clear direction for change, strengthens innovation, and improves internal trust. Personnel competencies particularly technical expertise, ethical conduct, and digital literacy contribute significantly to improving the quality of public service. A professional culture reduces behavioral deviations and enhances institutional legitimacy, while an effective oversight system promotes transparency, continuous evaluation, and accountability. The synergy of these four pillars forms a strategic framework that accelerates Polri’s reform agenda. The study concludes that strengthening human resource capacity is not merely a supportive component but a key catalyst for shaping a modern, responsive, and publicly trusted police institution.